PENGARUH PENDEKATAN INKUIRI TERBIMBING DIPADU DENGAN DIAGRAM ALIR TERHADAP TINGKAT PEMAHAMAN DAN HASIL BELAJAR SISWA KELAS XI IPA SMA MUHAMMADIYAH JAYAPURA PADA MATERI LAJU REAKSI - FEBRIAN ANDI HIDAYAT (Program Magister Pendidikan IPA, Program Pascasarjana Universitas Cenderawasih, 2018)
this study aims to determine the influence of guided inquiry approach combined with a flow diagram of the level of student understanding and of the student learning outcomes, and the improving student learning outcomes after learning use of guided inquiry approach combined with a flow chart. The results showed that : (1) a significant difference between guided inquiry approach combined with a flow diagram of the level of understanding of students with count of sig. 0,000 < 5 %, as well as the influence of 98.6%. (2) a significant difference between guided inquiry approach combined with a flowchart of the learning outcomes 1, 2, and 3 with sig. of count 0.000 < 5 % with the average percentage of the influence is 67.8 %. (3) an increase in the average learning outcomes of students from all three meetings, including in the medium category with a value of n-Gain an average of 0.616